Geometry Modified Square Edge Orifice Valve Study for Efficiency Gas Lift with Computational Fluid Dynamic (CFD) Method - Adam Fatchur Rohman; Sugiatmo Kasmungin; Dwi Atty Mardiana (Penerbitan Universitas Trisakti, 2019)
The gas lift lifting system is widely used as an artificial lift on the X Field, with an average depth of gas lift production wells of 3,000-3,500 ft. Design of 3 to 5 Gas lift Valves (GLV) designwith size of 1 inch is ussualy applied. While at the point of gas injection, the GLV square edge orifice is applied. The problem in the optimization of gas lift wells is the flow instability due to gas flow rate fluctuations, the limited volumetric gas injection and limited gas compressor pressure. With the limited compressor pressure, the lift flow and gas design speed is very dependent on the amount of pressure on the compressor, the production wells with limited injection pressure will result in a limited amount of gas injection, the square edge orifice requires a pressure difference of 40% to achieve the maximum gas flow rate. This study aims to find the modification of the GLV orifice geometry to improve the efficiency of the gas lift system so that it can get optimal production. This GLV design modification includes changing the GLV orifice geometry. Design studies using Computational Fluid Dynamic (CFD) simulations aim to analyze any changes in GLV geometry design to the performance of the gas flow rate in the orifice valve described in the valve performance curve. The design modification approach is in accordance with the GLV venturi orifice geometry and the availability of equipment for GLV modification. The CFD simulation results of the first modification geometry by increasing the orifice diameter from 0.25 to 0.5 inch with the condition of upstream 650 psig and downstream 625 psig pressure increasing the injection gas flow rate capacity by 355% and modifying the second geometry with the venturi orifice form by 280%. In modifying the shape of the orifice venture to reach critical flow requires a pressure difference of 10%. Based on simulation results, the modified orifice application is able to increae production up to 44%.